Voluntary assurance of sustainability reporting: evidence from an emerging economy. Issue 2 (6th February 2020) - Hassan, Abeer; Elamer, Ahmed A.; Fletcher, Mary; Sobhan, Nawreen
Abstract : Purpose: This paper aims to investigate the supply and demand side of sustainability assurance in Bangladesh. Design/methodology/approach: Drawing on signalling theory, a logistic regression model is used for a sample of 100 of the largest Bangladeshi companies to study the relationships between assurance, sustainability disclosure, industry membership and reporting format. Findings: Authors' results show that companies which produce more sustainability information are more likely to get their sustainability assured, to be from non-carbon intensive industries, and are more likely to integrate their sustainability information with the financial annual reports. Authors' results support the argument that organisations based in weaker legal environments are more likely to secure assurance as this adds to the credibility and reliability of sustainability reports. Research limitations/implications: This paper has limitations which raise some issues for future research. First, the authors have covered only large companies; therefore, future research could examine the differences between small and large companies in relation to assurance. Secondly, the authors' data consist of company sustainability disclosure information in the fiscal year 2015. Longitudinal studies are recommended to extend this research. Finally, future research could examine the moderating effects of geographical location on the relationship between assurance (and its providers) and other variables. Practical implications: The findings of this paper will prove valuable to practitioners and researchers. Practitioners, including assurance providers and sustainability reporting managers will benefit from authors' study as it covers both the demand and supply side characteristics of assurance. Researchers will benefit from the study as it investigates assurance practices in the developing country of Bangladesh. Originality/value: To the best of the authors' knowledge, this is the first study to examine both the supply and demand sides of sustainability assurance in Bangladesh. Authors also introduce reporting format when measuring the relationship between assurance and its determinant factors at micro level. The study also links assurance to signalling theory.